Hydro-Economic based Model of Damage and Loss Analysis of Winongo River Flood - Muhammad Rifki Hardika (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2017)
Winongo River experienced considerably high flow that caused overflows along the downstream part of the river and some inundation at the surrounding area. The inundation has reached up to 1 m spread over the Tegalrejo Sub-district of Yogyakarta City and swept two houses. This paper analyses the damage and loss due to the flood by taking into account the hydraulics phenomena and the economic impact at the inundation area. A hydraulics model has been developed to study the flow characteristics during the flood of Winongo River, especially in the river reach in Tegalrejo Sub-district. The hazard-induced damages in the flooded area were identified and the economic impacts were studied. Several related software have been utilized to analyse the damage and loss of the disaster, including the HEC-RAS 5.0, ArcGIS, HEC-GeoRAS and InaSAFE. Through the integration of the characteristics of both flood phenomena and the economic factor, the damage and loss were then analysed and the Average Annual Damage (AAD) of approximately IDR 88,750,000,000 was obtained.